New challenges in facing cyberchondria during the coronavirus disease pandemic. (August 2022) - Vismara, Matteo; Varinelli, Alberto; Pellegrini, Luca; Enara, Arun; Fineberg, Naomi A
Abstract : Cyberchondria (CYB) is characterized by excessive online searching for medical information and is associated with increasing levels of distress, anxiety, and interference with daily activities. As the use of digital devices and the Internet as a source of everyday information has increased, particularly during the current coronavirus disease (COVID-19) pandemic, so has CYB, becoming an object of interest to clinicians and researchers. The present review will provide an overview of the latest updates in CYB research. Emerging evidence draws attention to various vulnerability factors for developing CYB, including personal characteristics such as female gender, younger age, or a history of mental disorder, as well as engagement in particular forms of online behavior, such as increased use of social media, increased acceptance of online information, and information overload. Additionally, recent studies suggest that CYB may itself act as a mediating factor for increased COVID-19-related psychological burden. However, the data are still very sparse. Knowledge gaps include a universally accepted definition of CYB, severity thresholds to help differentiate nonpathological online health searches from CYB, as well as robustly evidence-based interventions. Highlights: Cyberchondria (CYB) is a compulsive form of Internet searching for health-related information. Females, younger individuals, and history of mental disorder represent risk factors for CYB. The coronavirus disease pandemic have affected online health-searches and likely CYB. Data on CYB are still very sparse and an universally accepted definition is missing. Preventative and therapeutic approaches need to be validated in randomized clinical trials.